Psychological Profile of Patients with Inflammatory Bowel Diseases: Comparative Analysis with Standard Indicators - M. Ilich; D. S. Zyuzina; T. G. Mikhaylichenko; O. Yu. Shchelkova (СибСкрипт)
Chronic inflammatory bowel diseases and their severe symptoms are a serious stress factor that affects the emotional and social status of patients. However, the role of psychological factors in the development, course, and treatment of inflammatory bowel diseases remains understudied. This comprehensive analysis of psychodiagnostic indicators of patients with inflammatory bowel diseases and the standard data for healthy people could facilitate targeted psychological assistance and effective treatment support. The research included 61 patients with inflammatory bowel diseases, 51 patients with Crohn’s disease, and 10 patients with ulcerative colitis (39.4 % men, 60.6 % women; 30.29 ± 9.94 y. o.) The psychodiagnostic methods and questionnaires included The State-Trait Anxiety Inventory, The Perceived Stress Scale, The Big Five Inventory, The Ways of Coping Questionnaire, and The Purpose in Life Test. The comparative analysis of emotional state indicators revealed strong situational anxiety (p < 0.001) and personal anxiety (p<0.001), as well as high subjective stress (p<0.001) and the overstrain indicator (p < 0.001). The analysis of basic personality traits showed that the traits measured by the self-awareness scale (p < 0.001) were more pronounces than those measured by the scales of extroversion (p < 0.01), emotional stability (p < 0.001), and personal resources (p < 0.01). The coping behavior test demonstrated self-control (p < 0.001), search for social support (p < 0.001), responsibility acceptance (p < 0.001), solution planning (p < 0.001), and positive reappraisal (p < 0.05). The male patients had low indicators for life goals (p < 0.001), life process (p < 0.001), life performance (p < 0.01), locus of I-control (p < 0.01), and the overall life purpose (p = 0.001). The women had low indicators (p < 0.05) for life process, which signified dissatisfaction with the current life situation. In general, the patients with inflammatory bowel diseases had a high level of emotional tension (anxiety and subjective stress), personal anxiety, and emotional instability, with responsibility and organization being the prevailing personality traits; they adhered to stereotypes and demonstrated a wide range of active coping strategies with poor personal coping resources, especially in men. The data obtained can be used to improve the psychological support of patients with inflammatory bowel diseases.